Clinical variability in neurohepatic syndrome due to combined mitochondrial DNA depletion and Gaucher disease - Julie Harvengt; Catherine Wanty; Boel De Paepe; Christine Sempoux; Nicole Revencu; Joél Smet; Rudy Van Coster; Willy Lissens; Sara Seneca; Laurent Weekers; Etienne Sokal; François-Guillaume Debray (Molecular Genetics and Metabolism Reports, 2014)
A 1-year-old girl born to consanguineous parents presented with unexplained liver failure, leading to transplantation at 19 months. Subsequent partial splenectomy for persistent cytopenia showed the presence of foamy cells, and Gaucher disease was confirmed by homozygosity for the p.Leu483Pro mutation in the GBA gene. She was treated by enzyme replacement therapy (ERT). Clinical follow-up showed mild developmental delay, strabismus, nystagmus and oculomotor apraxia. Biochemical studies revealed multiple respiratory chain deficiencies and a mosaic pattern of deficient complex IV immunostaining in liver and fibroblast. Molecular analysis identified a mtDNA depletion syndrome due to the homozygous p.Pro98Leu mutation in MPV17. A younger sister unaffected by mtDNA depletion, presented with pancytopenia and hepatosplenomegaly. ERT for Gaucher disease resulted in visceral normalization without any neurological symptom. A third sister, affected by both conditions, had marked developmental delay, strabismus and ophthalmoplegia but no liver cirrhosis. In conclusion, intrafamilal variability occurs in MPV17-related disease. The combined pathological effect of Gaucher and mitochondrial diseases can negatively impact neurological and liver functions and influence the outcome in consanguineous families. The immunocytochemical staining of OXPHOS protein in tissues and cultured cells is a powerful tool revealing mosaic pattern of deficiency pointing to mtDNA-related mitochondrial disorders.